The feasibility and acceptability of a virtual six-week psychoeducational intervention for carers of patients with heart failure. (29th July 2021) - Cassidy, L; Hill, L; Fitzsimons, D
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Northern Ireland Chest Heart and Stroke Queen"s University Belfast Background: Globally, the number of individuals living with heart failure (HF) is increasing, with many living with additional comorbidities and complex health needs. Carers play an invaluable role in helping the patient with self-care at home, taking on the key responsibility for tasks critical in the management and monitoring of HF symptoms. As a result, carers can frequently experience poor quality of life attributed to this caring role, whilst simultaneously managing health problems of their own. Evidence has shown that many of these carers have unmet educational, social and emotional needs, that require urgent support and information. Purpose: To assess the feasibility and acceptability of a six-week psychoeducational intervention tailored towards carers of patients with HF. Methods:   The psychoeducational intervention was co-produced with involvement of carers, HF professionals and researchers. It was delivered over six weeks, with four support group sessions and an information booklet tailored specifically to the needs of carers. Carers were identified by the clinical HF team or through social media, with informed consent obtained before inclusion. Due to COVID-19 regulations, the support group sessions were delivered virtually via a secure online app (Zoom). Each session involved a member of the interdisciplinary research team and covered topics including: 1. Understanding HF, 2. Personal wellbeing, 3. Communication and Support, and 4. Practical skills to help manage HF. Validated questionnaires (SF-12, HADS, ZBI, PSS, MSPSS, CPS) measuring carer related outcomes were completed at baseline, at 6 weeks and 3 months post intervention. Qualitative data from focus group post-intervention explored the acceptability of the intervention. Data was analysed using SPSS (version 27) and NVivo (version 11). Results:  Nine participants consented to participate, six of which were recruited from heart failure clinics, and three volunteered in response to social media advertisements. Two participants, due to personal health reasons, withdrew consent and did not attend the support group sessions. All carers were female, mean age 61 years, four spouses and three adult children. Preliminary qualitative findings show carers recalled information and advice included in the intervention as useful and easy to understand. With the intervention being described as, "a dimension that doesn't already exist". The majority of participants (n = 5) preferred the convenience and flexibility of the online approach to the intervention, however some participants (n = 2) felt that they would have benefitted more from an in-person approach. A second  support group is currently underway.  Conclusions: Preliminary results are promising and indicate that carers responded well to an online psychoeducational intervention.